A Clinical Report of Two Cases of Cryptogenic Brain Abscess and a Relevant Literature Review - Zhou, Wei; Shao, Xuefei; Jiang, Xiaochun (Frontiers in Neuroscience, 2019)
Brain abscess, a severe intracranial infectious disease, refers to the parenchyma abscess caused by local infection or remote spread. Recently, advancements in modern medicine, especially the wide application of antimicrobial drugs, have contributed to the gradual decrease in the prevalence of this disease. However, cases of cryptogenic brain abscess that feature an unknown origin and atypical symptoms are rising. In this retrospective study, we report and analyse two cases of cryptogenic brain abscess.